A Public Empire: Property and the Quest for the Common Good in Imperial Russia - Ekaterina Pravilova (Princeton University Press, 2014)
Europeâ€™s long nineteenth century (1789â€“1914) was rich with bold innovations and great disappointments. The rise of nationalism, the â€œsocial question,â€ feminism, and new models of public administration and economic policy were accompanied by the demise of well-established concepts. Such was the fate of individualism, defined by Anthony Arblaster as the â€œmetaphysical and ontological coreâ€ of classical liberalism.1 Individualism and its corollaryâ€”the principle of inalienable private propertyâ€”had been seen as the greatest conceptual achievement of post-revolutionary Europe. Yet by the end of the century, this crowning jewel of the liberal order found itself widely criticized and discredited in favor of more community-oriented, state-sympathetic, and social-minded doctrines. This ideological shift both reflected and contributed to a profound transformation of the state. The new state that evolved as a result is much more familiar to us than the â€œstate as watchdogâ€ ideal popularized by early-nineteenth- century liberals. Contrary to early liberal beliefs, government powers steadily increased over the nineteenth century, developing internally through the rationalization of the state apparatus, the professionalization of bureaucracies, and the influx of experts and technocrats. States also assumed new functions in the areas of welfare and social protection, economic regulation, and cultural guidance, while at the same time transferring many of their tasks to public organizations. As a result, government became at once more visible and transparent and more intrusive.2 The state was not, indeed, the only beneficiary of the decline in individualism: one of the most important and visible consequences of this development was the growth of the â€œpublicâ€ domain at the expense of private properties. Many objects and resources that had previously made up the bulk of the private wealth of Old Regime and post-revolutionary Europe changed hands and became regulated either by state agencies or by public organizations. Private ownership of publicly important things was restricted by multiple conditions drawn up by experts on the basis of â€œscientificallyâ€ established principles and enforced by the government. In the second half of the nineteenth century,one saw the development of public trusts owning erstwhile private estates now cherished as historical monuments. Acting on behalf of the nation, the state introduced new rules that limited the disposal of privately owned forests; wealthy landowners could not hunt on their own estates if the law designated their potential prey as protected species. Private owners had to agree to the ubiquitous taking of their properties for the construction of â€œpublicâ€ placesâ€”new streets, avenues, and squares, as well as publicly important railways and other means of communication. Liberals, however, did not perceive this growing intrusion as a threat to private freedoms: inalienable private property ceased to be the main and unconditional attribute of personal liberty, whereas the possibility to construct spaces for public life came to be seen as the prerequisite of the societyâ€™s collective freedom.